Karakteristik Musiman pada Kondisi Langit berdasarkan Clearness Index di Aceh Besar (Buletin GAW Bariri, 2022)
Knowledge of the sky conditions in particular location is a fundamental to studies about climate and has applications  for meteorology, industry, agriculture, architecture, engineering, studies of water resources development and solar energy conversion system. These conditions can be quantified by meteorological parameter such as the clearness index. Clearness index ( is defined as the ratio of global solar irradiance measured at ground level and its counterpart the extra – terrestrial radiation at the top of the atmosphere. In this study, seasonal characteristic of sky condition in Aceh Besar (05.4°S and 95.46°W) has been carried out using . One year (Jan 2020 – Dec 2020) measured data of daily average global radiation has been used to determines the daily and monthly variations of. The result shows that for daily averages,  ranges from 0.19 to 0.70 with cloudy days are common days in Aceh Besar with hardly any very clear days. For monthly average, the month of January shows the highest  (0.55), while November shows the lowest (0.41). Based on monthly averages of the daily, monthly percentage cumulative frequency, and climatic conditions, the sky condition in Aceh Besar is classified into two seasonal periods. The dry season (January – March and June – September) has values ranging between 0.44 and 0.55, while the wet season (April – May and October – December) has ranging between 0.44 and 0.45.